Relation of chemical and mechanical properties of Eucalyptus nitens wood thermally modified in open and closed systems. Issue 3 (4th May 2019) - Wentzel, M.; Fleckenstein, M.; Hofmann, T.; Militz, H.
ABSTRACT: In the present work, Eucalyptus nitens was thermally modified in an open (atmospheric pressure) and a closed (under pressure) reactor system. The effect of the changes of the chemical composition on the mechanical properties was investigated. Hemicelluloses, cellulose, lignin, extractives, acetic acid, formic acid, total phenols and the cellulose degree of polymerization (DP) as well as modulus of elasticity (MOE) and modulus of rupture (MOR) were measured for each modification. The results indicated that the closed system modification, particularly at high pressure, presented stronger variations on the chemical structure of the modified wood than the modifications in the open system. In both modifications, MOR showed a better correlation with the chemical changes than the MOE, especially xylose, cellulose DP, lignin and total phenols. These correlations suggest a tendency of a more brittle wood in the closed system modification at high pressure than in the modifications in the open system. Results can be used as a reference for future applications of thermally modified E. nitens wood.